Philanthropic Impact of Investing Via Waqf-Featured Unit Trust Funds Determinant Factors Influencing the Participation in Waqf Unit Trust Funds in Malaysia - Syahnaz Sulaiman; Syadiyah Abdul Shukor; Amalina Mursidi; Muhammad Ridhwan Ab. Aziz (International Shari’ah Research Academy for Isla, 2024)
Indexed by WOS/ Scopus